2017
DOI: 10.1088/1361-6528/aa583a
|View full text |Cite
|
Sign up to set email alerts
|

Sharpness-induced energy shifts of quantum well states in Pb islands on Cu(111)

Abstract: We elucidate that the tip sharpness in scanning tunneling microscopy (STM) can be characterized through the number of field-emission (FE) resonances. A higher number of FE resonances indicates higher sharpness. We observe empty quantum well (QW) states in Pb islands on Cu(111) under different tip sharpness levels. We found that QW states observed by sharper tips always had lower energies, revealing negative energy shifts. This sharpness-induced energy shift originates from an inhomogeneous electric field in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Thus, we know that the effective sharpness is 121.1°for the six resonances in figure 3(a) and 84.6°for the nine resonances in figure 3(b). Evidently, a larger number of FERs corresponds to higher effective sharpness, which is consistent with the results of our previous study [19].…”
Section: Effective Sharpness Of Stm Tipsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, we know that the effective sharpness is 121.1°for the six resonances in figure 3(a) and 84.6°for the nine resonances in figure 3(b). Evidently, a larger number of FERs corresponds to higher effective sharpness, which is consistent with the results of our previous study [19].…”
Section: Effective Sharpness Of Stm Tipsupporting
confidence: 93%
“…On the other hand, from the slope of the FEP in figure 2(b), it can be known that the electric field strength of the FERs is 0.29 V/Å. Consequently, the electric field of the field emission is stronger than that of FERs, which can be attributed to the sharpness of the STM tip that enhances the electric field near the tip but weakens that near the sample [19]. This situation is unable to be explained by the model in the inset in figure 2(a) where the STM tip is a plane.…”
Section: Effective Sharpness Of Stm Tipmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have explained that under the same current, more FERs result from a sharper STM tip. [22][23][24] Fig. 1(b) also shows that the higher-order peaks in the spectra with three and ve FERs are all much narrower than those in the spectra with four and six FERs.…”
Section: Resultsmentioning
confidence: 89%
“…21 The zero valley intensities appearing around the FER may indicate that the observed material has a band gap above the vacuum level. 21 The number of FERs can manifest the sharpness [22][23][24] and eld enhancement factor 25 of the STM tip. Previous studies have demonstrated that FER can be used to investigate the atomic structure of an insulator, 26 plasmon-assisted electron tunneling, 27 and the dynamics 28,29 and lateral quantization [30][31][32] of surface electrons above the vacuum level.…”
Section: Introductionmentioning
confidence: 99%